CTZ and Calcium Hydroxide Pastes Did Not Cause Hepatic and Renal Alterations in Mice - Cacilda Castelo Branco Lima; Marina de Deus Moura Lima; Marcia dos Santos Rizzo; Caroline Barros Oliveira; Airton Mendes Conde Júnior; Marcoeli Silva de Moura; Lúcia de Fátima Almeida de Deus Moura (Association of Support to Oral Health Research (APESB), 2024)
Objective: To evaluate the possible renal and hepatic alteration by root canal filling pastes in mice. Material and Methods: Fifty-four mice were divided into nine groups and received one polyethylene tube implant containing two filling pastes (CTZ or calcium hydroxide pastes). Empty polyethylene tubes were used as a negative control. All tubes were implanted subcutaneously in the back of the mice. After time intervals of 7, 21, and 63 days, 1.5 mL of blood was collected by cardiac puncture, and serum samples were used for serological testing. Urea, creatinine, aspartate transferase (AST), alanine transferase (ALT), alkaline phosphatase (ALP), and gamma-glutamyltransferase (GGT) were evaluated. Data were analyzed by 2-way ANOVA (p<0.05). Results: When comparing CTZ and calcium hydroxide pastes and empty tubes and experimental time intervals, no significant differences in the results were found for any of the biochemical parameters analyzed (p>0.05). No differences were observed in the interactions (material*experimental time intervals) and the biochemical parameters analyzed (p>0.05). Conclusion: CTZ and calcium hydroxide pastes did not cause hepatic and renal alterations in mice, demonstrating the pastes' safety.